Molecular analysis of blood-associated pathogens in European wildcats (Felis silvestris silvestris) from Germany. (December 2022) - Unterköfler, Maria Sophia; Harl, Josef; Barogh, Bita Shahi; Spergser, Joachim; Hrazdilová, Kristýna; Müller, Franz; Jeschke, Diana; Anders, Ole; Steinbach, Peter; Ansorge, Hermann; Fuehrer, Hans-Peter; Heddergott, Mike
Abstract: European wildcats ( Felis silvestris silvestris ) have not been investigated in large numbers for blood-associated pathogens in Germany, because wildcats, being a protected species, may not be hunted, and the collection of samples is therefore difficult. Thus, spleen tissue and whole blood from 96 wildcats from Germany found as roadkill or dead from other causes in the years 1998–2020 were examined for the prevalence of blood associated pathogens using molecular genetic tools. PCR was used to screen for haemotrophic Mycoplasma spp., Hepatozoon spp., Cytauxzoon spp., Bartonella spp., Filarioidea, Anaplasmataceae, and Rickettsiales, and positive samples were subsequently sequenced. Phylogenetic analyses were performed for Mycoplasma spp. and Hepatozoon spp. by calculating phylogenetic trees and DNA haplotype networks. The following pathogens were found: Candidatus Mycoplasma haematominutum (7/96), Mycoplasma ovis (1/96), Hepatozoon silvestris (34/96), Hepatozoon felis (6/96), Cytauxzoon europaeus (45/96), and Bartonella spp. (3/96). This study elucidates the prevalence of blood-associated pathogens in wildcats from Germany. Graphical abstract: Image 1 Highlights: European wildcats from Germany carry different blood-associated pathogens. Pathogens can also affect domestic cats. Transmision by vectors or other transmisison routes are possible.